2015
DOI: 10.1177/0308518x15594800
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic fixes: cyclical devaluation and accumulation through climate change impacts

Abstract: Abstract. This paper investigates the scales and temporalities through which climate change impacts may be rendered into socio-ecological fixes for crises of overaccumulation within the (re)insurance industry. The property insurance and catastrophe reinsurance sectors are notorious for their cyclicity, with prices and returns oscillating dramatically between "soft" and "hard" markets. The problem of overaccummulation in soft market periods is often resolved by the destruction of reinsurers' capital reserves th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 46 publications
1
57
0
Order By: Relevance
“…. as well as The Socioecological Fix: Fixed Capital, Metabolism, and Hegemony surplus production, is a condition for [fixed capital formation]" (707), and suggested that as the scale of infrastructure projects grow, so, too, must the size of the surpluses or the pot of fictitious capital generated 280 through credit and financial mechanisms with the latter increasingly representing the terrain on which fixes might be unfolding (see Johnson 2015). In this respect, the possibility of a fix is largely immanent to, albeit not determined by, crises of overaccumulation and 285 their associated surpluses.…”
Section: Fixed Capital As a Metabolic Processmentioning
confidence: 99%
“…. as well as The Socioecological Fix: Fixed Capital, Metabolism, and Hegemony surplus production, is a condition for [fixed capital formation]" (707), and suggested that as the scale of infrastructure projects grow, so, too, must the size of the surpluses or the pot of fictitious capital generated 280 through credit and financial mechanisms with the latter increasingly representing the terrain on which fixes might be unfolding (see Johnson 2015). In this respect, the possibility of a fix is largely immanent to, albeit not determined by, crises of overaccumulation and 285 their associated surpluses.…”
Section: Fixed Capital As a Metabolic Processmentioning
confidence: 99%
“…They too may be left to the state to handle, and a "splintering protectionism" generated in which increasing burdens are unequally felt by different citizens. 79 The author wishes to acknowledge, with gratitude, Asa Maron, Marion Fourcade, Neil Fligstein, Calvin Morrill, the participants of the GEMS seminar at the University of California, Berkeley, as well as the editorial board at Politics & Society, for their generative and valuable comments on earlier versions of this article.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, vulnerability can become entrenched in ghettos of uninsurable housing in high risk areas (Gearing, 2018;King et al, 2013). Johnson (2015) further suggests that the insurance industry uses large-scale extreme weather events as an opportunity to re-calibrate risk modeling and further increase premiums for high risk areas, leading to what she calls "splintering protectionism" in which the property of the affluent is secured against loss, while the vulnerable are left to hope for ad hoc disaster relief by governments. Affordable or not, there is currently little empirical evidence to support the effectiveness of risk-reflective pricing as a risk signal (McAneney et al, 2013), or risk perception as a driver of insurance purchase (Bubeck et al, 2012).…”
Section: Problematic Privatization Of Climate Adaptationmentioning
confidence: 99%